AKW101 - Introduction to Management - August - September 1998 - PPP, Pusat Pengajian Pengurusan (1998)
Bachelor of Computer Science (Hons) External Degree USM Programme (In Collaboration with Universiti Sains Malaysia) August/September 1998 AKW101 - Introduction to Management Time : [2 hours]